Пейзажі рівнинного району дендропарку “Тростянець”: “Велика Галявина” - Ilyenko, A.A.; Medvedev, V.A.; Nesterenko, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Changes in a composition of landscapes, number and a species structure of arboreal plantations of the Big Glade of dendropark Trostyanets, which have taken place during last 50 years are analyzed. Decorative design is described, the taxonomic and phytocoenotic characteristic of grassy cover are given. Measures of restoration of the disturbed compositions are planned.